Cancer of Eden: A Novel on Parental Absence in a Child’s Development - Jenscellin Febiola Wijaya; Dwi Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2025)
Up until today, the cases of absent parents are still rising, and many are still unreported. This problem may be caused by the lack of understanding of its effect on children, where parents undermine the importance of caring and nurturing their children. With this case in mind, this creative thesis explores the effects of parental absence in a child’s development, the way their parents or caretaker react, and how the children overcome their psychosocial and emotional troubles. By using John Bowlby’s Attachment Theory, we can recognize the different patterns on different children after being raised without parental figures. This issue will be explored using the dystopian genre and novel form to show how the absence of parents can cause the child characters to be emotionally detached, feel helpless, and seek attention. The reason for these behaviors come from the fact that the children are abandoned by their supposed-caretakers, the aliens, and now live on their own in the facility. At the end, the children are able to tackle their problems by communicating with each other, regulating their emotions, and becoming self aware of their issues.